Concise legal dictionary (Delhi, 1997)
The Concise Law Dictionary is a handy and compact law dictionary that provides accurate meaning of legal terms, and other words and phrases commonly used in various fields of law. The present edition includes judicial interpretation from the latest landmark as well as other important decisions of the Supreme Court and the various High Courts. This edition also includes entries extracted from recent enactments such as the Criminal Law (Amendment) Act 2013, the Companies Act 2013, the National Food Security Act 2013, the Lokpal and Lokayuktas Act 2013, and the Pension Fund Regulatory and Development Authority Act 2013. This dictionary incorporates terms and phrases related to the emerging areas of law such as Information Technology, Intellectual Property Rights, Alternate Dispute Resolution, Cyber Law, Forensic Medicine, International Trade and Commerce as well as areas of social relevance.
Keywords: Dictionaries